2013
DOI: 10.1186/1743-8977-10-24
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular fate of carbon nanotubes inside murine macrophages: pH-dependent detachment of iron catalyst nanoparticles

Abstract: BackgroundCarbon nanotubes (CNT) are a family of materials featuring a large range of length, diameter, numbers of walls and, quite often metallic impurities coming from the catalyst used for their synthesis. They exhibit unique physical properties, which have already led to an extensive development of CNT for numerous applications. Because of this development and the resulting potential increase of human exposure, an important body of literature has been published with the aim to evaluate the health impact of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 41 publications
2
22
0
Order By: Relevance
“…Although this dose might be high with regards to the lung burden which might be reached after inhalation exposure (Basich et al 2014;gangwal et al 2011;landsiedel et al 2010), it is a relatively low dose in the context of an in vitro study required to understand the role of p53 following NM exposure. Furthermore, it has been shown that in vitro studies can be a good indicative of in vivo response dependant on the NM and the investigated specific outcome (cho et al 2013;gaiser et al 2012;Kermanizadeh et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this dose might be high with regards to the lung burden which might be reached after inhalation exposure (Basich et al 2014;gangwal et al 2011;landsiedel et al 2010), it is a relatively low dose in the context of an in vitro study required to understand the role of p53 following NM exposure. Furthermore, it has been shown that in vitro studies can be a good indicative of in vivo response dependant on the NM and the investigated specific outcome (cho et al 2013;gaiser et al 2012;Kermanizadeh et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The MNM granularity and aggregation status were evaluated in material suspensions via photon correlation spectroscopy (PcS) and zeta potential measurements, respectively (Zetasizer 300HS, Malvern, UK). In order to calculate the purity of the MWcNT a TgA analysis was performed (Bussy et al 2013). The main physicochemical characteristics are summarised in Table 1.…”
Section: Manufactured Nanomaterials Characterisation and Treatmentmentioning
confidence: 99%
“…This later study, like others discussed previously with respect to cellular targeting following assimilation, highlighted the potential importance of the lysosome in the internal fate of assimilated ENPs. In particular it was noted that blockage of intracellular lysosomal acidification prevented the Fe 3 C ENPs detachment from CNT bundles and protected cells from CNT downstream toxicity (Bussy et al 2013).…”
Section: Secondary Ion Mass Spectrometry Micro Particle Induced X-ramentioning
confidence: 99%
“…To achieve our aim, we synthesized, following a dedicated initial process, four MWCNT specifically devoted to our study and differing in length, and that were functionalized to concomitantly modify their surface chemistry and/or iron content (Additional file 1: Figure S1): S-CNT (short), SF-CNT (short and functionalized), L-CNT (long) and LF-CNT (long and functionalized), functionalized CNT (SF- and LF-CNT) having a different iron content from their non-functionalized counterpart (S- and L-CNT) (Table 1). The biodegradation of these CNT was addressed in RAW 264.7 murine macrophages in vitro, by the mean of Raman spectroscopy performed on CNT recovered in cells, after 3 different exposure time points; 6, 24 or 48 h. Moreover, as we recently demonstrated that pH could be an important player in the fate of CNT inside cells [19], we also investigated the role of pH in CNT biodegradation process. Our results demonstrate that MWCNT can be biodegraded inside macrophages, in a time-dependent manner, via an intracellular pH-dependent biological mechanism.…”
Section: Introductionmentioning
confidence: 99%